Implementation of Fiqih Private Vocational School Learning in the Covid-19 Pandemic Period in Mis Katingan - Titin Alia Husnah (Green Publisher Indonesia, 2021)
The Covid-19 pandemic, which requires learning to be carried out online, has made the implementation of learning in Jurisprudence subjects not run optimally. This research was conducted with the aim of knowing how the implementation of online learning in fiqih subjects during the Covid -19 pandemic in MIS, Katingan Hilir District, Katingan Regency. This research is a descriptive qualitative research. The data taken from this study is data that is relevant to the research focus, namely on online learning of fiqh subjects during the Covid -19 pandemic in MIS, Katingan Hilir District, Katingan Regency. The collected data will be analyzed using several stages, preparation, analysis, presentation of the results of the analysis. The results of this study indicate the learning implementation strategy used by the teacher in fiqh learning during the Covid 19 pandemic at MIS Katingan Hilir was carried out by a strategy planning board. The use of learning methods is centered on methods that are bold through the material sent by the teacher. The media used are multimedia-based media in the form of a powerpoint module and the whatsapp group and google classroom media communication platform. After planning by the teacher about learning then the teacher implements the strategy, pre-learning activities are carried out in the form of question and answer interactions.